Purification and characterization of a Ca2+-dependent novel lectin from Nymphaea nouchali tuber with antiproliferative activities - Ranajit Kumar Shaha (2011)
A lectin (termed NNTL) was purified from the extracts of Nymphaea nouchali tuber followed by anion-exchange chromatography on DEAE-cellulose, hydrophobic chromatography on HiTrap Phenyl HP and by repeated anion-exchange chromatography on HiTrap Q FF column. The molecular mass of the purified lectin was 27.0 +−1.0 kDa, as estimated by SDS/PAGE both in the presence and in the absence of 2-mercaptoethanol. NNTL was an o-nitrophenyl β-Dgalactopyranoside sugar-specific lectin that agglutinated rat, chicken and different groups of human blood cells and exhibited high agglutination activity over the pH range 5–9 and temperatures of 30–60◦C. The N-terminal sequence of NNTL did not show sequence similarity with any other lectin and the amino acid analysis revealed that NNTL was rich in leucine, methionine and glycine residues. NNTL was a glycoprotein containing 8% neutral sugar and showed toxicity against brine shrimp nauplii with an LC50 value of 120 +− 29 μg/ml and exerted strong agglutination activity against four pathogenic bacteria (Bacillus subtilis, Sarcina lutea, Shigella shiga and Shigella sonnei). In addition, antiproliferative activity of this lectin against EAC (Ehrlich ascites carcinoma) cells showed 56% and 76% inhibition in vivo in mice at 1.5 and 3 mg·kg−1·day−1 respectively. NNTL was a divalent ion-dependent glycoprotein, which lost its activity markedly in the presence of denaturants. Furthermore, measurement of fluorescence spectra in the presence and absence of urea and CaCl2 indicated the requirement of Ca2+ for the stability of NNTL.